2010
DOI: 10.1002/lapl.201010089
|View full text |Cite
|
Sign up to set email alerts
|

Generation of 244-fs pulse at 1044.7 nm by a diode-pumped mode-locked Yb:Y2Ca3(BO3)4 laser

Abstract: We report a passively mode-locked Yb:Y2Ca3(BO3)4 (Yb:CYB) laser with a partially reflective semiconductor saturable-absorber mirror. The minimum pulse duration of 244-fs with a repetition rate of ∼ 55 MHz has been obtained at the central wavelength of 1044.7 nm (8.1 nm full width at half maximum (FWHM)). The measured average output power amounts to 261 mW under the absorbed pump power of 7.0 W. To our best knowledge, this is the first demonstration of a femtosecond Yb:CYB laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Such broad FWHMs suggested that Yb:CLB crystal should possess great potential in the generation of ultra-short pulse lasers. Its isomorphism Yb:CYB had been used to generate an ultra-short pulse laser with pulse width of 244 fs [14].…”
Section: Polarized Spectra Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such broad FWHMs suggested that Yb:CLB crystal should possess great potential in the generation of ultra-short pulse lasers. Its isomorphism Yb:CYB had been used to generate an ultra-short pulse laser with pulse width of 244 fs [14].…”
Section: Polarized Spectra Calculationmentioning
confidence: 99%
“…Recently, the thermal properties and passively Q-switched laser performance of the Yb:Ca 3 La 2 (BO 3 ) 4 crystal were studied by Pan [12]. The multi-wavelength continuous-wave (cw) and mode-locked lasers have been demonstrated with Yb:Ca 3 Gd 2 (BO 3 ) 4 (Yb:CGB) and Yb:Ca 3 Y 2 (BO 3 ) 4 (Yb:CYB) crystals [13,14]. In this paper, we report the comparison of the continuous wave laser performances of the Yb:Ca 3 La 2 (BO 3 ) 4 crystals along the three crystallographic axes.…”
Section: Introductionmentioning
confidence: 99%
“…The borate family with general formula M 3 R 2 (BO 3 ) 4 (M = Ca, Sr, Ba; R = La-Lu, Y) were first described by Dzhurinskii et al [12], a lot of Nd-doped M 3 R 2 (BO 3 ) 4 crystals have been investigated in detail, and they showed good laser properties [13][14][15]. Furthermore, many of Yb 3+ -doped M 3 R 2 (BO 3 ) 4 crystals have been reported to present broad emission bands with the FWHM larger than 60 nm [16][17][18][19][20][21][22], which mean that they are promising ultrashort pulse laser crystals, such as Yb 3+ :Ca 3 Y 2 (BO 3 ) 4 crystal, a pulse duration of 244 fs ultrashort laser was obtained by passively mode-locked technology [22].…”
Section: Introductionmentioning
confidence: 96%
“…In the lattice, the La and Ca ions randomly replace each other generating their disordered structure [10]. Recently, a minimum pulse duration of 244-fs with a repetition rate of 55 MHz was obtained in the isomorph Yb:Ca 3 Y 2 (BO 3 ) 4 (Yb:CYB) crystals [11]. The average linear thermal expansion coefficients, thermal diffusivity and thermal conductivity were measured along the a-, b-, and c-axis in [12], indicating that CLB crystal should have a high damage threshold.…”
Section: Introductionmentioning
confidence: 99%